Spatio-temporal variability of a chlorophyll-a based biomass index and influence of coastal sources of enrichment in the Algerian Basin. (1st January 2022) - Harid, Romaissa; Demarcq, Hervé; Keraghel, Mehdia-Asma; Ait-Kaci, Malik; Zerrouki, Mohamed; Bachari, Nour-El-Islam; Houma, Fouzia
Abstract: This study investigates the spatial distribution and temporal variability of chlorophyll- a (Chl- a ) biomass in the Algerian Basin (AB) along its meridional and cross-shore dimensions, focusing on coastal enrichments. After correcting most atmospheric disturbances in the daily MODIS Level-2 data series between 2003 and 2018, a fortnightly climatology of 1-km resolution Chl- a has been generated to account for specific coastal features previously poorly evidenced from 4-km Level-3 data. The AB is characterised by two extreme seasons of high and low biomass, separated by sharp transitions, that characterise the offshore domain. The coastal area (<10 km) reveals an intense and distinct dynamic associated with highly productive local hotspots rather than seasonal variability. A biomass index is proposed as the horizontally integrated Chl- a concentration from the coastline to the most offshore extension of the 0.5 mg m -3 Chl- a isopleth. This index separately quantifies the cumulative biomass of both offshore and coastal domains with large alongshore variability. Low values (<5 g m -2 ) were observed in the offshore area during summer and high values during the spring blooms (up to 40 g m -2 ), while maximum values (>50 g m -2 ) were locally observed in the coastal domain. The narrow coastal area alone represents 44% of the total biomass, with coastal hotspots where the enrichment is up to 5 times higher than offshore. Multivariate modelling of the potential factors favouring coastal enrichments shows that the phytoplanktonic biomass in coastal waters is mainly associated with enrichments from wadis and seasonally from city sewage as well as by the presence of a bay. A separate source of enrichment is undoubtedly associated with the presence of aquaculture cages. Highlights: A specific climatology of Chl- a has been generated over the AB from MODIS Level-2 data to explore the coastal domain. The AB is characterised by high and low biomass, sharp transitions, while the coastal area reveals a separated dynamic. Discontinuous and intense coastal cross-shore gradients reveal specific coastal sources of enrichments. A Chl- a based integrated index was defined to determine the importance of coastal enrichments. The Chl- a in coastal waters is mainly associated with enrichments from wadis and cities with a pronounced seasonal effect.